THE FACTORS CONTRIBUTING IN SPIRITUALITY DEFINITION OF IRANIAN MOSQUES - Ahmadzadeh Siyahrood, Sanaz; Ebrahimi, Arghavan; Ghiasvand, Javad; Mahdavinejad, Mohammadjavad (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
Islamic mosques in Iran, similar to other Islamic nations, are reflections of visual beauties and typical examples of symbolic integration and relationship with strong beliefs and geometry. Scrutiny of these relationships provides a broader and profound perception of the design paradigm of these sacred masterpieces, which not only have been responding to the functional aspect of holy places but also represent an aesthetic model of architectural geometric perfection. This paper aims to survey this paradigm with a focus on its basic concepts and geometric origins; in this regard, it seeks to address the ensuing questions: what are the fundamental ideas in the design of mosques? How and which methods were used have been reflected in the architecture of mosques? How has the geometry assisted the architecture of mosques? What is the geometry role in the accomplishment of those basic concepts? To this end, after stating the fundamental concepts and dominant ideology in the design of mosques and the progress factors of Islamic architecture, their architectural features, spatial organization, and relations with geometry had been examined. The research hypothesis is that monotheism and divine unity are the original concepts of the architecture of mosques and this type of architectural design tries with the help of a range of abstract arts, symbolic materials, various methods, and science of geometry symbolize these ideas to create a sacred atmosphere and place which could be an intermediate spot for the human to achieve that divinity and unity.